2013
DOI: 10.3892/ol.2013.1501
|View full text |Cite
|
Sign up to set email alerts
|

An aggressive form of non-Hodgkin's lymphoma with pleural and abdominal chylous effusions: A case report and review of the literature

Abstract: Serous effusions, including pleural, abdominal and pericardial effusions, are complications of lymphoma. Among these types, pleural effusions are the most common to be observed. However, the involvement of the abdominal or pericardial cavity is rare. An impairment of the lymphatic drainage and direct infiltration have been identified to play significant roles in effusion formation. Multiple techniques, including cytological exams, immunochemistry and cytogenetics, have been applied in the clinic to access the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 21 publications
0
10
0
Order By: Relevance
“…Recently, the data of lymphoid neoplasms in effusions are lacking from many parts of the world. It has been reported mostly as single case description or in reviews of multiple case reports from different institutions [20][21][22][23][24]. To the best of our knowledge, this study is the largest series of lymphoid neoplasms in effusions reported from China.…”
Section: Discussionmentioning
confidence: 97%
“…Recently, the data of lymphoid neoplasms in effusions are lacking from many parts of the world. It has been reported mostly as single case description or in reviews of multiple case reports from different institutions [20][21][22][23][24]. To the best of our knowledge, this study is the largest series of lymphoid neoplasms in effusions reported from China.…”
Section: Discussionmentioning
confidence: 97%
“…Malignant pericardial effusion associated with NHL may represent direct malignant infiltration, effusive-constrictive pericarditis secondary to radiation therapy, invasion of the pericardial space with opportunistic pathogens or an inflammatory effusion secondary to chemotherapy [ 2 , 5 ], as we suspect was the case in our patient after his third effusion recurrence. In two-thirds of cases, pericardial effusion is a benign complication, and not an extension, of malignancy [ 6 ]. A lymphocyte-rich effusion may represent a reactive lymphocytosis indistinguishable from malignancy, but this equivocal yield can be overcome by using morphometry with 85% sensitivity and 95% specificity [ 2 ].…”
Section: Discussionmentioning
confidence: 99%
“…Pleural fluid cytology also showed that the fluid was a metastasis from lymphoma cells into the pleuralspace. 18 The diagnosis of a high risk of venous thromboembolism (VTE) in patients is based on Padua scoring the total score of 9. This patient should be given prophylactic heparin but considering that the patient has thrombocytopenia so it cannot be given.…”
Section: Case Reportmentioning
confidence: 99%